Relação entre desemprego e aversão ao risco: uma análise do mercado de trabalho de Fortaleza - Ce - Gonçalces, Jivago Ribeiro (2014)
The job search theory predicts that more risk averse individuals have lower wages than less risk-averse individuals booking and therefore would be less likely to be unemployed (PISSARIDES, 1974; NACHMAN, 1975; LIPPMAN and McCALL, 1976). Empirical evidence for this hypothesis, however, are quite scarce in labor in developed and practically nonexistent in countries with markets characterized by a high degree of informality country markets. This paper aims to investigate this theory in the latter context, and more specifically for the market of Fortaleza, CE (Brazil), using for this purpose a database containing information of the labor market, along with indicators of risk behavior of individuals . From this database, classified themselves as individuals to risk aversion, there were estimates of the probability of unemployment from logit models, and met results consistent with the theory, especially when comparing individuals with this condition those in the informal market.